Recent advances and future perspectives of sol-gel derived porous bioactive glasses: a review - Deshmukh, Kalim; Kovářík, Tomáš; Křenek, Tomáš; Docheva, Denitsa; Stich, Theresia; Pola, Josef (RSC advances, 2020)
The sol-gel derived porous bioactive glasses have drawn worldwide attention by virtue of the convenience and flexibility of this versatile synthesis method. In this review, the recent advances in sol-gel processed porous bioactive glasses in biomedical fields, especially for bone tissue regeneration applications have been comprehensively reviewed. Generally, it is envisaged that the morphology and chemical compositions of sol-gel derived porous bioactive glasses significantly affect their biological properties. Therefore, the controlled synthesis of these porous glasses is critical to their effective use in the biomedical fields. With this context, the first part of the review briefly describes the fundamentals of the sol-gel technique. In the subsequent section, different approaches frequently used for the sol-gel synthesis of porous glasses such as microemulsion and acid-catalyzed based synthesis have been reviewed. In the later part of the review, different types of sol-gel derived bioactive glasses namely silica, phosphate and silica-titania based glasses along with organic-inorganic hybrids materials have been discussed. The review also discusses the chemical, surface, mechanical and biological properties and further highlights the strategies to control the pore structure, shape, size and compositions of sol-gel derived bioactive glasses. Finally, the review provides a detailed discussion about the bone tissue regeneration application of different types of sol-gel derived bioactive glasses and presents future research perspectives.